Cajuput (Melaleuca cajuputi (L.) Powell) Oil Yield and Cineole Analysis in Ex-Coal Mining Land with Monoculture and Agroforestry Patterns - Anna Juliarti; Nurheni Wijayanto; Irdika Mansur; Trikoesoemaningtyas (Jurnal Sylva Lestari, 2022)
Cajuput (Melaleuca cajuputi) has the potential to be developed with monoculture and agroforestry patterns in ex-coal mining land. This study aimed to analyze the oil yield and cineole content of cajuput planted with monoculture and agroforestry and patterns in ex-coal mining land. The research design used a split-split plot design with three factors: planting pattern, fertilizer dosage, and lemongrass (Cymbopogon nardus) plant spacing. The variables measured included the oil yield and cineole content of cajuput. This study was conducted in cajuput monoculture and agroforestry patterns with lemongrass G2 variety and Sitrona 2 Agribun variety, with various spacing. The study was conducted for six months, with one harvest of cajuput leaves in the sixth month. The results showed that lemongrass's planting pattern and plant spacing significantly affected cajuput oil yield. However, treatment of the dosage of fertilizer had no significant effect on cajuput oil yield. The treatment of lemongrass plant spacing only significantly affected cineole content, but planting patterns and fertilizer dosages had no significant effect. The cajuput agroforestry with the Sitrona 2 Agribun variety produced the highest oil yield (2.84%) and cineole content (50.70%), compared to the monoculture pattern and cajuput agroforestry with G2 variety. The lemongrass plant spacing of 0.5 m x 0.5 m produced the highest oil yield (2.73%) and cineole content (52.98%) compared to 1 m x 1 m plant spacing Cymbopogon nardus. Keywords: agroforestry, cineole, essential oil, ex-coal mining, Melaleuca cajuputi